Innovating Leadership in the Digital Age: Transformational Approaches to Navigate the Convergence of Emerging Technologies and Organizational Change. A Case Study of Bank XYZ - Michelle (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study examines the role of transformational leadership at XYZ in facilitating digital innovation, with an emphasis on the in corporation of technologies including artificial intelligence (AI), mobile banking, and big data analytics. This study employs qualitative analysis of XYZ’s annual and sustainability reports to illustrate how leadership has cultivated an innovative and adaptable culture, enabling the bank to integrate digital solutions and sustain a competitive advantage. The study highlights the significance of change management strategies, such as Lewin’s, Kotter’s, ADKAR, and McKinsey’s 7S, in addressing technology disruption and organizational resistance. XYZ's leadership adopted digital technologies and aligned them with strategic objectives, thereby ensuring regulatory compliance and enhancing operational efficiency. The findings indicate that future banking leaders must manage technological disruption while promoting ongoing innovation. The study provides actionable recommendations for leadership, technology adoption, and change management applicable to financial institutions aiming for success in digital transformation.